2023
DOI: 10.3389/fphar.2023.1091978
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance on cannabidiol as an antiepileptic agent

Abstract: Introduction: Cannabidiol (CBD) is an active chemical contained in the plant Cannabis sativa. It is a resorcinol-based compound that crosses the blood-brain barrier without causing euphoric effects. CBD has a plethora of pharmacological effects of therapeutic interest. CBD has been authorized in the European Union as an anticonvulsant against serious infantile epileptic syndromes, but its safety profile is still not sufficiently described.Methods: With the goal of expanding information on the safety of CBD use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Despite the growing popularity of this substance, a complete safety profile of CBD has not been drawn. However, CBD can produce several adverse effects, as it has been observed in children treated for seizures refractory to other drugs (Ammendolia et al, 2023). Some of these adverse effects include raising in temperature, but also convulsions (Devinsky et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing popularity of this substance, a complete safety profile of CBD has not been drawn. However, CBD can produce several adverse effects, as it has been observed in children treated for seizures refractory to other drugs (Ammendolia et al, 2023). Some of these adverse effects include raising in temperature, but also convulsions (Devinsky et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this data bank, SARs to IL‐23 inhibitors guselkumab, risankizumab, and tildrakizumab are described in individual case safety reports (ICSRs), similar to other drugs. Spontaneous signaling of SARs involves medical events that have been observed following the use of a drug, but are not necessarily caused by the same medicine 8 . In the EudraVigilance system, all ICSRs are signaled by healthcare or nonhealthcare professionals.…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneous signaling of SARs involves medical events that have been observed following the use of a drug, but are not necessarily caused by the same medicine. 8 The primary outcome of interest was the analysis of ICSRs reporting malignancies as SARs related to the IL-23 inhibitors guselkumab, risankizumab, and tildrakizumab in-3 years 2020-2021-2022. The odds ratio, its 95% confidence interval, and sex difference were calculated using reporting odds ratio (ROR) method.…”
Section: Me Thodsmentioning
confidence: 99%
“…CBD has a favorable safety profile in humans [ 18 , 20 ], in rats [ 210 ], and in dogs [ 211 ]. A recent pharmacovigilance study concluded that CBD is a safe compound that causes only rare adverse reactions [ 212 ]. However, like any other drug, it is not innocuous; the adverse effects reported in humans so far could vary in severity and include somnolence, fatigue, gastrointestinal ailments, such as diarrhea, vomiting, and changes in appetite/weight, among others [ 213 ].…”
Section: Therapeutic Evidence Involving Cbdmentioning
confidence: 99%
“…Finally, CBD action on hepatic enzymes needs to be consider since it can modify the pharmacokinetics of other drugs. A pharmacovigilance study concluded that CBD–drug interactions must be highly considered, since CBD is indicated in people with ongoing treatments, some of them as aggressive as chemotherapy [ 212 ].…”
Section: Therapeutic Evidence Involving Cbdmentioning
confidence: 99%